Upaya Meningkatkan Aktivitas Belajar Siswa dalam Pembelajaran IPA Melalui Model Pembelajaran Kooperatif Tipe Jigsaw di SMP Negeri 7 Bukittinggi Provinsi Sumatra Barat - Nilawati Nilawati (Jurnal Paedagogy, 2021)
This study aims to increase student learning activities in science learning through the Jigsaw type learning model at SMPN 7 Bukittinggi. This research method used classroom action research which is carried out in 2 cycles. The instrument used is an observation sheet. The data analysis technique of this research used quantitative and qualitative descriptive analysis. The results of this study indicate that based on the results of the first cycle of student activity in bringing source books/reading 50.3%, cooperation in groups 59.6%, expressing opinions in large groups 35.7%, working on questions in groups 45.7%, pointing to hands answered the quiz 24%. While in the second cycle there was a significant increase, in the aspect of bringing source books/reading 67.5%, cooperation in groups 74%, expressing opinions in large groups 59%, working on questions in groups 76%, and pointing hands to answer quizzes 65% . This shows that the learning activities of grade VII-8 students of SMPN 7 Bukitinggi are in the high category. So it can be concluded that the Jigsaw type learning model can improve student learning activities in science learning.